Minawisata as Integrated Fisheries-Based Tourism: Development Potential in Kampung Madong–Sei Nyirih, Indonesia - Winata Wira; Muzahar Muzahar; Falmi Yandri; Oksep Adhayanto; Bismar Arianto (CV. Austronesia Akademika, 2025)
This study examines the development potential and carrying capacity of minawisata (fisheries-based marine tourism) in Kampung Madong–Sei Nyirih, Tanjungpinang City, Kepulauan Riau Province, in response to growing demands for sustainable coastal development and alternative livelihoods for fishing communities. The research aims to evaluate land suitability, environmental carrying capacity, and infrastructure readiness for three main clusters: mangrove ecotourism, fishing tourism, and floating net cage aquaculture. A mixed-methods approach was applied, combining Geographic Information Systems (GIS)-based spatial analysis, carrying capacity calculations aligned with national regulatory standards, and qualitative input from government, community, academic, and private stakeholders. The results revealed that 66.03% (199.42 ha) of mangrove areas and 99.13% (322.47 ha) of marine waters are highly suitable for tourism activities, while only 1.0% of the assessed areas are suitable for floating net cage aquaculture. Carrying capacity estimates showed the potential to accommodate 1,595 daily visitors for mangrove-based tourism, 1,075 for fishing activities, and 45 for aquaculture tourism. These findings underscore significant opportunities for developing integrated fisheries-tourism models, especially through mangrove conservation and traditional fishing practices that align with sustainable tourism principles. However, challenges remain in addressing infrastructure gaps, institutional coordination, and community capacity for tourism service delivery. The study concludes that Kampung Madong–Sei Nyirih holds strong potential as a model for sustainable coastal development that integrates conservation, economic diversification, and community empowerment. Its implementation could provide practical lessons for similar coastal regions in Indonesia and Southeast Asia facing the dual challenges of environmental protection and livelihood improvement